Complete endoscopic sphincterotomy with vs. without large-balloon dilation for the removal of large bile duct stones: randomized multicenter study - Karsenti, David; Coron, Emmanuel; Vanbiervliet, Geoffroy; Privat, Jocelyn; Kull, Eric; Bichard, Philippe; Perrot, Bastien; Quentin, Vincent; Duriez, Arnaud; Cholet, Franck; Subtil, Clément; Duchmann, Jean Christophe; Lefort, Christine; Hudziak, Hervé; Koch, Stéphane; Granval, Philippe; Lecleire, Stéphane; Charachon, Antoine; Barange, Karl; Cesbron, Elodie Metivier; De Widerspach, Axel; Le Baleur, Yann; Barthet, Marc; Poincloux, Laurent (Endoscopy, 2017)
Background and study aims Endoscopic sphincterotomy plus large-balloon dilation (ES-LBD) has been reported as an alternative to endoscopic sphincterotomy for the removal of bile duct stones. This multicenter study compared complete endoscopic sphincterotomy with vs. without large-balloon dilation for the removal of large bile duct stones. This is the first randomized multicenter study to evaluate these procedures in patients with exclusively large common bile duct (CBD) stones.Methods Between 2010 and 2015, 150 patients with one or more common bile duct stones ≥ 13 mm were randomized to two groups: 73 without balloon dilation (conventional group), 77 with balloon dilation (ES-LBD group). Mechanical lithotripsy was subsequently performed only if the stones were too large for removal through the papilla. Endoscopic sphincterotomy was complete in both groups. Patients could switch to ES-LBD if the conventional procedure failed.Results There was no between-group difference in number and size of stones. CBD stone clearance was achieved in 74.0 % of patients in the conventional group and 96.1 % of patients in the ES-LBD group (P < 0.001). Mechanical lithotripsy was needed significantly more often in the conventional group (35.6 % vs. 3.9 %; P < 0.001). There was no difference in terms of morbidity (9.3 % in the conventional group vs. 8.1 % in the ES-LBD group; P = 0.82). The cost and procedure time were not significantly different between the groups overall, but became significantly higher for patients in the conventional group who underwent mechanical lithotripsy. The conventional procedure failed in 19 patients, 15 of whom underwent a rescue ES-LBD procedure that successfully cleared all stones. Conclusions Complete endoscopic sphincterotomy with large-balloon dilation for the removal of large CBD stones has similar safety but superior efficiency to conventional treatment, and should be considered as the first-line step in the treatment of large bile duct stones and in rescue treatment.Trial registered at ClinicalTrials.gov (NCT02592811).